2009
DOI: 10.1038/nn.2250
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine reverses cocaine-induced metaplasticity

Abstract: Cocaine addiction is characterized by an impaired ability to develop adaptive behaviors that can compete with cocaine seeking, implying a deficit in the ability to induce plasticity in cortico-accumbens circuitry critical for regulating motivated behavior. RWe found that rats withdrawn from cocaine self-administration had a marked in vivo deficit in the ability to develop long-term potentation (LTP) and depression (LTD) in the nucleus accumbens core subregion following stimulation of prefrontal cortex. N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
402
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 366 publications
(431 citation statements)
references
References 51 publications
26
402
3
Order By: Relevance
“…Glutamatergic synaptic transmission to dopamine neurons is a key site of plasticity [32][33][34][35][36][37][38][39][40] , and both stress and cocaine directly target NMDARs, which in turn can modulate AMPAR-mediated synaptic transmission 11 . Studies of the effects of acute stress on glutamatergic transmission have shown that such stress enhances synaptic strength by increasing AMPAR trafficking or AMPARmediated excitatory transmission in various brain regions, including midbrain dopaminergic neurons, the prefrontal cortex and the NAc shell [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Glutamatergic synaptic transmission to dopamine neurons is a key site of plasticity [32][33][34][35][36][37][38][39][40] , and both stress and cocaine directly target NMDARs, which in turn can modulate AMPAR-mediated synaptic transmission 11 . Studies of the effects of acute stress on glutamatergic transmission have shown that such stress enhances synaptic strength by increasing AMPAR trafficking or AMPARmediated excitatory transmission in various brain regions, including midbrain dopaminergic neurons, the prefrontal cortex and the NAc shell [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…drug-induced behaviors such as sensitization, CPP, and reinstated drug-seeking (Achat-Mendes et al, 2007;Moussawi et al, 2009;Muriach et al, 2010;Numa et al, 2008).…”
Section: Potential Role Of Cocaine-induced Protein S-glutathionylationmentioning
confidence: 99%
“…Here, repeated administration of cocaine blunts cystine-glutamate exchange, leading to reduced basal and increased cocaine-induced glutamate in the nucleus accumbens that persists for at least 3 weeks after the last cocaine treatment (Baker et al, 2003). Most compelling is the observation that treatment with N-acetylcysteine, by activating cystine-glutamate exchange, prevented cocaineinduced escalation and behavioral sensitization, restored the ability to induce LTP and long-term depression in the nucleus accumbens, and blunted reinstatement in animals and conditioned reactivity to drug cues in humans (Moussawi et al, 2009;LaRowe et al, 2007;Madayag et al, 2007).…”
Section: Molecular Targets For Neuroplasticity: Binge/intoxication Wmentioning
confidence: 99%